Framing Anti-Bullying Da'wah Messages in Local Radio Talkshow - Izza Afkarina; Ahmad Arifulin Nuha (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Bullying is a pervasive social issue requiring ethical communication responses across various environments. Specific Background: Local radio, such as the Jelita Talkshow on LPPL Radio Suara Lumajang, functions as a medium for integrating religious values into discussions of social problems. Knowledge Gap: There is limited research on how anti-bullying da'wah messages are constructed through media framing based on Islamic communication ethics. Aims: This study analyzes the construction of anti-bullying messages using Robert N. Entman’s framing analysis from an Islamic communication ethics perspective. Results: The findings indicate that bullying is framed as a social problem with moral and spiritual dimensions, emphasizing ethical communication, collective responsibility, and Qur’anic values. The causes are linked to weak ethical awareness and permissive environments, while solutions focus on moral education and polite communication. Novelty: This study offers a framing-based perspective on da'wah messages in local radio grounded in Islamic ethics. Implications: The results highlight the role of local radio as a contextual da'wah medium in fostering ethical awareness and supporting Islamic communication studies. Highlights: Media narratives position harmful behavior as a collective moral concern grounded in spiritual values. Identified causes include low ethical literacy and permissive social environments. Proposed approaches emphasize moral education and polite interaction across social contexts. Keywords: Preaching, Bullying, Framing Analysis, Islamic Communication Ethics, Radio